The impact of financial crisis on Kazakhstan economy and possible solutions - Toktamys, Zhibek (My University, 2021)
Bu tez finansal krizleri açıklayarak Kazakistan ekonomisi üzerindeki etkilerini inceleyecektir. Finansal krizler hem ülke bazında hem de küresel çapta meydana gelebilmektedir.Finans krizi ekonomide durgunluk, üretim sürecinin daralması ve yaşam standardın bir bozulma anlamına gelmektedir. Her bir ülkede krizlerin niteliği, etkisi aşamalarına göre farklılık gösterir. Bu bağlamda finansal krizlerin etkisine yönelik tek bir açıklama getirilemez. Finansal krizleri derinlemesine anlayabilmek için krizleri hangi faktörlerin, ön koşulların krizlerini belirlediğini ortaya koymak, bu süreçlerin teorik ve metodolojik temellerini belirlemek gerekir. Finansal krizlerin geriye yönelik incelemesi olmadan da bu gerçekleştirilemez. Bu açıdan tez finansal krizleri teorik olarak ortaya koyarak Kazakistan ekonomisi üzeirndeki etkilerini ortaya koyacak ve finansal krizlerin bu ekonomi üzerindeki etkilerini azaltmak için öneriler sunacaktır.

The thesis will explain the financial crisis and examine their effects on economy of Kazakhstan. Financial crisis can ocur both on a country basis and on a global scale. The financial crisis stagnation in the economy, countraction of the production process and a deteroiation of the living standard. The nature of the crisis in each country differs according to the stage of their impact. In this context no single explanation can be given the regarding to impact of financial crisis. In order to understand financial crisis in depth, it is necessary to reveal which factors and preconditions determine crisis and to determine crises theoretical and methodological foundation of these process. This cannot be achieve without retrospective analysis of financial crisis. From this point of view, the thesis will put forward the effects of financial crisis on the economy of Kazakhstan by putting forth theoretically and will offer suggestions to reduce the effects of financial crisis on this economy.
Keywords: Büyüme Financial Crisis; Crisis Theories; Economic crisis; Economics, Kazakhstan; Ekonomi, Kazakistan; Ekonomik kriz; Finance; Finansal Kriz; Growth; Kriz Teorileri; Maliye